Clinical Practice Approach to Nonalcoholic Fatty Liver Disease by Pediatric Gastroenterologists in the United States. Issue 2 (February 2019) - Shapiro, Warren L.; Yu, Elizabeth L.; Arin, Jennifer C.; Murray, Karen F.; Ali, Sabina; Desai, Nirav K.; Xanthakos, Stavra A.; Lin, Henry C.; Alkhouri, Naim; Abdou, Reham; Abrams, Stephanie H.; Butler, Megan W.; et al.
ABSTRACT: Objectives: Nonalcoholic fatty liver disease (NAFLD) is common; however, no information is available on how pediatric gastroenterologists in the United States manage NAFLD. Therefore, study objectives were to understand how pediatric gastroenterologists in the US approach the management of NAFLD, and to identify barriers to care for children with NAFLD. Methods: We performed structured one-on-one interviews to ascertain each individual pediatric gastroenterologist's approach to the management of NAFLD in children. Responses were recorded from open-ended questions regarding screening for comorbidities, recommendations regarding nutrition, physical activity, medications, and perceived barriers to care. Results: Response rate was 72.0% (486/675). Mean number of patients examined per week was 3 (standard deviation [SD] 3.5). Dietary intervention was recommended by 98.4% of pediatric gastroenterologists. Notably, 18 different dietary recommendations were reported. A majority of physicians provided targets for exercise frequency (72.6%, mean 5.6 days/wk, SD 1.6) and duration (69.9%, mean 40.2 minutes/session, SD 16.4). Medications were prescribed by 50.6%. Almost one-half of physicians (47.5%) screened for type 2 diabetes, dyslipidemia, and hypertension. Providers who spent more than 25 minutes at the initial visit were more likely to screen for comorbidities ( P = 0.003). Barriers to care were reported by 92.8% with 29.0% reporting ≥3 barriers. Conclusions: The majority of US pediatric gastroenterologists regularly encounter children with NAFLD. Varied recommendations regarding diet and exercise highlight the need for prospective clinical trials. NAFLD requires a multidimensional approach with adequate resources in the home, community, and clinical setting.